„Prejudices on the Scholarly Standards of Historiography“: A Brief Note in the Margins of the „Dispute“ over the Th ird Edition of Dějiny českého a slovenského dějepisectví by Kutnar and Marek - Horský, Jan (Dějiny – teorie – kritika, 2010)
Th is paper responds in a discussive manner to a critical review by Miloš Havelka of the third edition of František Kutnar‘s and Jaroslav Marek‘s book Přehledné dějiny českého a slovenského dějepisectví, published in Dějiny – teorie – kritika 6/2009, pp. 380–387.